2010
DOI: 10.1111/j.1464-5491.2010.02971.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pain and association with quality of life, depression and glycaemic control in patients with diabetes

Abstract: Aims To determine the prevalence of pain and its association with glycaemic control, mental health and physical functioning in patients with diabetes.Methods Cross-sectional data from a multi-site, prospective cohort study of 11 689 participants with diabetes. We analysed the associations of pain severity and interference with glycated haemoglobin (HbA 1c ) measurements and Medical Outcomes Study SF-Mental and Physical Component Summary-12 (MCS-12 and PCS-12) scores.Results Of participants, 57.8% reported mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 27 publications
0
45
3
Order By: Relevance
“…Our relationships with high HbA1C levels further suggest diabetes mellitus, especially uncontrolled, needs to be considered as a potential risk factor for cough, particularly in the elderly population. There is still a paucity of studies investigating the associations between HbA1c and non-diabetic, or non-cardiovascular conditions; however, high HbA1c was positively related to reflux symptom episodes in adolescents [34], and also was independently associated with the increased prevalence of pain [35,36]. …”
Section: Discussionmentioning
confidence: 99%
“…Our relationships with high HbA1C levels further suggest diabetes mellitus, especially uncontrolled, needs to be considered as a potential risk factor for cough, particularly in the elderly population. There is still a paucity of studies investigating the associations between HbA1c and non-diabetic, or non-cardiovascular conditions; however, high HbA1c was positively related to reflux symptom episodes in adolescents [34], and also was independently associated with the increased prevalence of pain [35,36]. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly, pain and depression commonly coexist. It has been shown that there is a 2.5-10 times increase in anxiety or major depression in patients with pain, 4 that pain in diabetes is strongly associated with depression (P<0.001), 5 and that the onset of depression is associated with an increasing number of pain locations (P<0.001) and higher severity of pain (P<0.001). 6 Furthermore, there is concern that presence of pain negatively affects recognition and treatment of depression: depressed patients are more likely to present with pain symptoms than low mood.…”
Section: Pain and Depressionmentioning
confidence: 99%
“…In patients with metabolic disorders, symptoms of fatigue were found to concern primarily the dimensions of general and physical fatigue [30]. Similar to fatigue, sleep disorders and pain were found to concern a significant proportion of patients with metabolic alterations (above 60%), with a greatest prevalence in obese subjects [31,32,33]. …”
Section: Prevalence Of Behavioral Symptoms In Metabolic Disordersmentioning
confidence: 99%